Maxillofacial fracture trauma: orbital walls fracture and their association using multilayer neural network perspectives - Wan Ahmad, Wan Muhamad Amir; Shaari, Ramizu; Mohd Noor, Nor Farid; Adnan, Mohamad Nasarudin; Nizam Akbar, Nurul Asyikin; Aleng, Nor Azlida; Mohamad Ghazali, Farah Muna; Abdul Halim, Nurfadhlina; Mohd Ibrahim, Mohamad Shafiq; Mustapa, Nurul Husna; Yaqoob, Muhammad Azeem; ,; et al. (New York Business Global LLC, 2022)
Objective: This study aims to find the association of fractured orbital walls with other possible fractures reported in the maxillofacial trauma cases in the Oral Maxillofacial Clinic Oral Maxillofacial ward, Hospital USM Kelantan, Malaysia. Materials and methods: From 2013 to June 2018, records of patients who sustained maxillofacial fractures and presented them to the Accident and Emergency Department, Oral Maxillofacial Clinic, Hospital USM were reviewed, recorded, and analyzed. Data were obtained from 294 patients who met the study's eligibility requirements. The medical records of every patient with a comprehensive medical history were reviewed. The following factors were studied: age, gender, zygomatic arch, maxillary sinus, orbital wall, symphysis of the mandible, parasymphysis, and the condyle. The broken orbital walls in these patients were examined in detail. In the first stage, all of the variables that have been picked will be assessed for their significance from a clinical standpoint. All potential factors contributing to the orbital wall fracture were analyzed using the SPSS and R studio programs. As a result of meeting the inclusion criteria, 294 patients' data has been gathered. Each patient who had a complete medical record was subjected to an examination. In these patients, the cracked orbital walls were examined in greater depth. All chosen variables will be tested in the first stage to see if they are clinically significant. Results: The participants in this study were 228 men (77.6%) and 66 women (22.4%). It was found that the most common age ranges are 11-20 years (39.8%), 21-30 years, and 31-40 years (26.2%). According to Spearman correlation, all of the studied variables have a significant association, with a p-value of less than 0.05. According to the findings of the multiple logistic regression, it was discovered that gender is significant, Zygomatic Arch fracture, Maxillary Sinus, Symphysis of the mandible, the condyle of the mandible, the body of the mandible, and the angle of the mandible. The validation of the factor through the Multilayer Neural Network (MLNN) and the accuracy obtained 97.71% with the predicted mean square error (PMSE) 0.159%. Conclusion: The matrix spearman correlation, multiple logistic regression, and neural network uncovered a clear association between orbital wall fracture and several other parameters. This discovery will help researchers understand the most common orbital wall fracture causes in maxillofacial trauma.